Systematic Literature Review: Efektivitas Penggunaan Media Pembelajaran Berbasis Augmented Reality pada Pembelajaran Biologi - Peliya Anesha; Irwandani; Meita Dwi Solviana (Program Studi Pendidikan Biologi, FKIP, Universitas Nusa Nipa, 2026)
The development of digital technology in the field of education encourages the use of Augmented Reality as an interactive learning medium, especially in biology learning that involves many abstract concepts. However, research findings on the effectiveness of Augmented Reality are still diverse and have not been thoroughly integrated. The purpose of this study is to analyze how effective the use of Augmented Reality-based learning media is in improving student learning outcomes, learning motivation, and their understanding of biological concepts. The Systematic Literature Review method with a qualitative approach was used in this study. This research was conducted through searching the Google Scholar, Crossref, and Scopus databases with the Publish or Perish application from 2021 to 2025. The PRISMA 2020 guidelines were used to analyze 23 articles that met the inclusion criteria. The results of the study show that students' learning outcomes, motivation, and understanding of concepts in biology learning can be improved with the use of Augmented Reality. Learning becomes more engaging, meaningful, and engaging thanks to Augmented Reality's ability to visualize abstract material into more concrete through interactive 3D displays. This research also provides implications and contributions to the development of science, especially in the field of educational technology, by strengthening empirical evidence on the effectiveness of Augmented Reality and becoming a reference in the development of innovative and adaptive digital technology-based biology learning models and media.